2007
DOI: 10.1016/j.bbalip.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The Sec14-superfamily and the regulatory interface between phospholipid metabolism and membrane trafficking

Abstract: A central principle of signal transduction is the appropriate control of the process so that relevant signals can be detected with fine spatial and temporal resolution. In the case of lipid-mediated signaling, organization and metabolism of specific lipid mediators is an important aspect of such control. Herein, we review the emerging evidence regarding the roles of Sec14-like phosphatidylinositol transfer proteins (PITPs) in the action of intracellular signaling networks; particularly as these relate to membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 66 publications
1
62
0
Order By: Relevance
“…Similar results were observed for clavesin 2 in neurons and for both clavesin 1 and 2 ectopically expressed in HeLa cells (data not shown). The Sec14 Domain of Clavesin 1 Binds PtdIns(3,5)P 2 -Sec14 domains generally function in lipid binding (21,22). Preliminary studies with PIP strips indicated that the Sec14 domain of clavesin 1 and 2 bound to phosphorylated forms of PtdIns but not PtdIns alone or other phospholipids, such as phosphatidylcholine or phosphatidylserine (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were observed for clavesin 2 in neurons and for both clavesin 1 and 2 ectopically expressed in HeLa cells (data not shown). The Sec14 Domain of Clavesin 1 Binds PtdIns(3,5)P 2 -Sec14 domains generally function in lipid binding (21,22). Preliminary studies with PIP strips indicated that the Sec14 domain of clavesin 1 and 2 bound to phosphorylated forms of PtdIns but not PtdIns alone or other phospholipids, such as phosphatidylcholine or phosphatidylserine (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Sec14p is composed of the Sec14 domain only, whereas the majority of Sec14 proteins in mammals contain a Sec14 domain in conjunction with other modules or protein/lipid binding domains (21,22). In the few well characterized examples, these proteins function to integrate lipid binding/metabolism with other biological functions (21,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The association of transiently increased neural PtdCho (in OP-dosed mice) with degeneration confined to the longest spinal axons and of sustained PtdCho elevation (in NTE-cKO mice) with increasing areas of axonal damage suggests a linkage between neural PtdCho homeostasis and axonal maintenance. In yeast, PtdCho homeostasis and constitutive secretion are linked via the phospholipid-binding protein, sec14p (Mousley et al, 2007). Axonal maintenance depends on membrane trafficking and microtubule-based transport.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, oxysterol-binding proteins might function as sensors rather than transporters (Raychaudhuri and Prinz, 2010). A role as sensors in regulating vesicular transport has been proposed for PI-transfer proteins in yeast (Mousley et al, 2007).…”
Section: Lipid Transportmentioning
confidence: 99%